PELATIHAN KONSEP,PEMOTONGAN ,PELAPORAN DAN JURNAL AKUNTANSI PERPAJAKAN PAJAK PENGHASILAN PASAL 21 ATAS PEGAWAI TETAP - Tyas Pambudi Raharjo; Liem Yan Sugondo; RA.Hera Purnami Kusumasari (JURNAL PENGABDIAN MANDIRI, 2022)
Taxpayers in Indonesia in completing their tax obligations use a self-assessment system where the taxpayer performs calculations, reports, and deposits independently on the tax payable, so every taxpayer needs an understanding and mastery of taxation to create this. The role of the teacher is very important to advancing education. The problem faced by teachers, especially tax accounting teachers, is the lack of information regarding training in the concept of withholding reporting and recording in the form of accounting journals, especially in Income Tax 21 for permanent employees to produce reliable report products. PKM implementation methods are counseling and training, mentoring methods, and coaching methods. This PKM aims for (1) teachers will understand the concept and legal basis of Income Tax Article 21 (2) teachers will understand the procedure for calculating, withholding, and journalizing PPh 21 taxes (3) and inputting into the ESPT system for precise and accurate reporting needs. The target of the output of PKM activities is published in the national mass media and campus media, as well as appropriate technology in the form of SPT 1721 Income Tax Article 21 reports